A Systematic Review of Strategic Brand Management in Educational Institution: Towards an Integrative Approach - Toetik Wulyatiningsih; Deske W. Mandagi (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study presents a comprehensive systematic review that delves into the multifaceted elements underpinning strategic brand management within the educational context. The primary objective was to examine and synthesize evidence-informed exploration, shedding light on the essential components of strategic brand management in educational institutions. Utilizing a systematic literature review (SLR) methodology, we meticulously extracted and screened 25 scientific articles from the Scopus and Web of Science (WOS) databases. The results of the data analysis spotlight the critical elements of strategic brand management within the educational context, underscoring their influential presence in shaping the educational landscape. These underlying elements comprise: (1) strategic partnerships with industry and alumni, (2) continuous improvement, adaptation, and innovation, (3) community engagement and public relations, and (4) an exceptional student, faculty, and staff experience.